2005
DOI: 10.1177/1098611103260558
|View full text |Cite
|
Sign up to set email alerts
|

Community Policing: The Middle Manager’s Perspective

Abstract: Community policing has evolved as the new organizational orthodoxy of policing. Volumes have been written on the subject by academics and research scholars. However, the voices of those who are charged with the reorganization of their departments and the implementation of community policing have been relatively silent. This article presents data drawn from the content analysis of the written views of community policing held by a select sample of middle managers from across the country. The respondents were att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…All the evaluations commented on the need for an effective and informed champion in middle management. This finding chimes with the lessons of research into the implementation of police innovations such as team policing (Sherman, Milton, & Kelly, 1973;Walker, 1993), problem solving and hot spotting (Irving & Dixon, 2002;Sherman et al, 2014), community policing (Vito, Walsh, & Kunselman, 2005), mental health diversion programs (Reuland, 2004), and domestic violence experiments (Sherman, 1992). In addition, it was quite apparent that the more effective programs operated within a strategic framework in which encouraged multiagency efforts that had been agreed by senior management across the agencies concerned (Haines et al, 2012;ICPR, 2012).…”
Section: Individualizing Gateway Triage By Offenses and Defendantssupporting
confidence: 69%
“…All the evaluations commented on the need for an effective and informed champion in middle management. This finding chimes with the lessons of research into the implementation of police innovations such as team policing (Sherman, Milton, & Kelly, 1973;Walker, 1993), problem solving and hot spotting (Irving & Dixon, 2002;Sherman et al, 2014), community policing (Vito, Walsh, & Kunselman, 2005), mental health diversion programs (Reuland, 2004), and domestic violence experiments (Sherman, 1992). In addition, it was quite apparent that the more effective programs operated within a strategic framework in which encouraged multiagency efforts that had been agreed by senior management across the agencies concerned (Haines et al, 2012;ICPR, 2012).…”
Section: Individualizing Gateway Triage By Offenses and Defendantssupporting
confidence: 69%
“…Even with this work to conceptualise COP performance measures, empirical studies suggest that departments with a COP approach may still be struggling with implementation (Vito et al ., 2005) and measurement. Lilley and Hindjua (2006, 2007) found that, of the 600 municipal and county policing agencies surveyed, many continue to use enforcement stats, and only some have developed additional COP performance measures.…”
Section: Challenges Of Police Performance Appraisalmentioning
confidence: 99%
“…Many criminal justice scholars, acceding to the reform tradition, find there is no set paradigm to replicate, and thus no scientific way to evaluate the model, as it tries to be all things to all people, becoming a rather amorphous idea of having a friendly police presence in the neighborhood with no organizational guidelines. A major scholarly criminal justice problem with this model has been trying to define just what a community is, so that it is possible to decide if the police are policing the community according to its norms and values (Strecher 2006;Vito et al 2005;Hunter and Barker 1993;Klockars 1979;Mastrofski 1991;Skolnick and Bayley 1986;.…”
Section: Resultsmentioning
confidence: 99%